The prevalence and clinical features of atrial fibrillation in heart failure patients with midrange ejection fraction in the Turkish population - Kivrak, T. Tarik; Kis, M.; Guzel, T.; Kaplan, M.; Kocabas, U.; Dogdus, M.; Bolayir, H. A. (Wiley, 2021)
[Abstract Not Available]